Rational Decision-Making for the Beneficial Application of Additive Manufacturing - Deppe, G.; Koch, R.; Kaesberg, M. (28th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing is a technology that offers a high potential forindustrial companies.Nevertheless, companies lack experience with this new technology and face the problem to identify processes where a successful and beneficial application can be achieved. They have to be supported in this analysis with a decision support tool which is capable to compare different manufacturing or repair approaches in order to determine the optimal solution for the correspondent use case. This is not always driven solely by costs but can also be critically affected by further influencing factors. This is why the decision support takes into account also time and quality alongside the costs. For a time-critical spare part supply, for example within aerospace sector, they are substantial for taking a decision. The presented decision support features a multi-attribute decision-making approach for selecting the most appropriate process, either Additive Manufacturing, conventional technologies or an external procurement.